Physics and Dynamics of Clouds and Precipitation - Wang, Pao K. (Cambridge : Cambridge University Press, 2013)
This key new textbook provides a state-of-the-art view of the physics of cloud and precipitation formation, covering the most important topics in the field: the microphysics, thermodynamics and cloud-scale dynamics. Highlights include: the condensation process explained with new insights from chemical physics studies; the impact of the particle curvature (the Kelvin equation) and solute effect (the Köhler equation); homogeneous and heterogeneous nucleation from recent molecular dynamic simulations; and the hydrodynamics of falling hydrometeors and their impact on collision growth. 3D cloud-model simulations demonstrate the dynamics and microphysics of deep convective clouds and cirrus formation, and each chapter contains problems enabling students to review and implement their new learning. Packed with detailed mathematical derivations and cutting-edge stereographic illustrations, this is an ideal text for graduate and advanced undergraduate courses, and also serves as a reference for academic researchers and professionals working in atmospheric science, meteorology, climatology, remote sensing and environmental science.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Cloud physics; Precipitation (Meteorology)